Web-Based Cashier Management, Inventory, And Sales Management Application Design - Muhammad Khotibul Umam; Tutik Khotimah; Ahmad Jazuli (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The rapid development of information technology has had a significant impact on various industries, including the retail sector. However, Atika Store still relies on manual methods in managing its cashier and inventory, leading to inaccuracy, inefficiency, and poor control over stock and sales reports. To address these issues, this study employs an applied research method aimed at producing practical solutions that can be directly implemented. A web-based application is developed using the Waterfall system development method, which consists of requirement analysis, system design, implementation, testing, and maintenance. The system integrates sales, inventory management, and cashier functions into a single platform. Key features include automatic receipt printing, sales transaction recording, real-time stock updates, and role-based user access. It is expected that this system will help MSME owners improve operational productivity, minimize manual errors, and support more effective decision-making.